Os sentidos da experi??ncia da peregrina????o para os andarilhos dos Passos de Anchieta - Nunes, Denise Bacellar (2016)
Pilgrimages in contemporary times have been a fruitful field for the development of research in various areas of human knowledge. However, even accompanied by important subjective and intersubjective components, the impact of this phenomenon on psychic life has not yet been studied in Psychology. This study aims at investigating the meanings that the systematic and continuous practice of the pilgrimage has for the subject who lives in the Passos de Anchieta, an event that reconstructs the historical journey made by the Jesuit saint Jos?? de Anchieta, in the Captaincy of the Holy Spirit, in the century XVI. The route begins in the state capital, Vit??ria, and travels about 100 km along the coast. The experience draws attention to the fact that it started 18 years ago with a small group of friends and, today, count on the participation of 4,000 wanderers. The intention of the research is to unveil the meaning of pilgrimage to the wanderer, seeking in the notion of meaning, in consonance with the phenomenology of Husserl and Merleau-Ponty, the foundations for the understanding of the phenomenon. The qualitative and exploratory methodology integrates two instruments, ethnography and semi-structured interviews, both also inspired by the phenomenological method. The first stage, of ethnographic description, was made with 4,000 participants in 24 hours of description. In the second stage, six wanderers were interviewed, following the following themes / axes: description of the history of the phenomenon; Meanings and impressions about the Steps of Anchieta; Experiences and reports of significant experiences obtained during the Passos de Anchieta; Transformations along the route and expectations and future projects in the Passos de Anchieta. From the results of the two instruments used, syntheses were made and, from them, variant and invariant sense units were presented. The analysis of the results was dialogued with the theoretical framework of work and other interdisciplinary theories. The results revealed that the senses that the pilgrims find in the experience are related to the corporality and that the pilgrims understand the phenomenon assigning meanings and meanings in diverse expressive modalities of sense that are as incarnated in several experiences of the way, in the form of sensations, Perceptions, directions, spiritualities, religiosities, belongings, feelings, sensibilities, spatialities, landscapes, meanings, teleologies. The journey unfolds in the sense of immanence and transcendence. It is also characterized, often in rituals, that it can include elements of a nature that are both metaphorical and of symbolic efficacy, and often accompanied by a cathartic effect. We conclude that, since experience is a vehicle for expressing belief its meanings and incarnated meanings in the body, it can not be merely reduced to the mere network of articulations, structures and sounds, but understood as the expressive plenitude of being in the world in a Continuous process of communication with the world and its derivations to the wanderers??? psychic health.